Three types of grab starts for competitive swimming - Counsilman, J. E.; Counsilman, B. E.; Nomura, T.; Endo, M. (Swimming Science V, 1979)
The purpose of this study was to compare the three starts: the scoop start, the flat start, and the track start. In all three of these starts the grab position was used by all subjects. Two groups were studied: Group A consisted of 37 male college swimmers and Group B of 121 male and female swimmers, aged 10 through 17 years.